STAKEHOLDERS’ ROLES IN THE ESTABLISHMENT OF BUM DESA IN SEMARANG DISTRICT - Sri Rahayu; Nunuk Supraptini (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
The establishment of BUM Desa (Badan Usaha Milik Desa - village enterprises) on the basis of the people’s initiative is needed to improve the people prosperity.Village independece will be achieved if village institutions concern on the village potential in developing enterprise through BUM Desa. The village head as the policy maker needs to expand the partnership in order to direct the business atmosphere into managerialprofessionalism and capital development. Eventually, the profit can be maxed to solve village problems.